A STUDY ON USING WEB CONTENT MANAGEMENT SYSTEMS IN UNIVERSITY SPORTS CLUB - Jayeseri Vasuthaven; Palvinderjit Kaur (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this paper is to present and elaborate the benefits of using Web Content Management Systems in university sports club. Sports clubs are those associations that lack the resources required to create and sustain a web presence. Unfortunately, many non-IT students currently lack the technical skills to create their own web application. Content Management Systems can avoid these issues by eliminating the need to teach PHP,HTML, SQL, etc., and allowing non-IT students to concentrate on content management that is important for university sports clubs. Web Content Management Systems are clarified, preceded by a concise WordPress overview. Examples are provided, together with university experiences.